Benefit of Intracystic Bleomycin for Symptomatic Recurrent Rathke Cleft Cyst. Issue 3 (16th November 2018) - Ung, Timothy H; Yang, Michael; Wang, Mary; Harland, Tessa; Lillehei, Kevin O
Abstract: BACKGROUND: Management of recurrent Rathke cleft cysts (RCC) is problematic. The mainstay of treatment has been reoperation with cyst drainage. Radical cyst resection, although effective, results in a high incidence of diabetes insipidus. Several case reports suggest a potential benefit to radiation therapy or the use of intracystic bleomycin. The intracystic application of bleomycin is known to be beneficial in the treatment of cystic craniopharyngioma; however, its usefulness in the treatment of recurrent RCC has yet to be proven. OBJECTIVE: To present our 6-yr experience using intracystic bleomycin for recurrent RCC. METHODS: We performed a retrospective chart review of patients with RCC who underwent surgical resection between January 2010 and May 2016 by a single surgeon. Specific attention was paid to patients with recurrent RCC. RESULTS: Of the 59 patients operated on for RCC during this 6-yr interval, 6 patients with symptomatic recurrent RCC were identified and received intracystic bleomycin at the time of reoperation. To date, no symptomatic cyst recurrence has been documented in the patients receiving bleomycin (mean = 38.8 mo, range 21.2-79.8 mo). CONCLUSION: The use of intracystic bleomycin appears to be a safe and potentially effective treatment option in patients with recurrent RCC. Additional studies with longer follow-up are needed to further define the role of bleomycin in recurrent RCC.